THE INNOVATIVE ROLE OF DIGITALIZATION MOTIVATES SMES MAINTAIN PRODUCTS BASED ON LOCAL CULTURE: (Research on Songket Woven Fabric SMEs in Sidemen Village, Klungkung District, Karangasem Regency, Bali Province) - R. Adjeng Mariana Febrianti; Thesa Aprilia (Lembaga Penelitian Universitas Pasundan, 2022)
Bali has a variety of customs, cultures that are different from other regions, traditional characteristics are expressed in a songket cloth which is full of meaning and contains a very deep meaning. The work of each region has its own style and variety, where the songket cloth from Sidemen Village has unique characteristics, especially the appearance of motifs and colors, so that they are used as the advantages of regional products. This study purposes to increase competitiveness through digitalization which motivates SMEs to maintain their local culture through product differentiation, innovation, customer relationship management and customer value based on local wisdom. Samples were taken from 150 SMEs of songket cloth using the sampling method and analyzed by SEM (Structural Equation Modeling) model. The results of the study conclude that product differentiation and innovation have an influence on customer value through customer relationship management. Suggestions are proposed that the maximum value for customers by developing continuous innovation without losing the characteristics of Bali with all its creativity in building a positive image, so that it can contribute to business continuity, especially SMEs.